The history of the conquest of New Spain - Díaz del Castillo, Bernal, 1496-1584 (University of New Mexico Press, 2008)
The History of the Conquest of New Spain by Bernal Diaz del Castillo, a new abridgement of Diaz del Castillo's classic Historia verdadera de la conquista de Nueva España, offers a unique contribution to our understanding of the political and religious forces that drove the great cultural encounter between Spain and the Americas known as the "conquest of Mexico." Besides containing important passages, scenes, and events excluded from other abridgements, this edition includes eight useful interpretive essays that address indigenous religions and cultural practices, sexuality during the early colonial period, the roles of women in indigenous cultures, and analysis of the political and economic purposes behind Diaz del Castillo's narrative. A series of maps illuminate the routes of the conquistadors, the organization of indigenous settlements, the struggle for the Aztec capital of Tenochtitlan, as well as the disastrous Spanish journey to Honduras. The information compiled for this volume offers increased accessibility to the original text, places it in a wider social and narrative context, and encourages further learning, research, and understanding.